PERAN LIMA PILAR PENGEMBANGAN PARIWISATA TERHADAP KAWASAN NUSA PENIDA, KLUNGKUNG - A. A. Gede Wijaya; I Putu David Adi Saputra; I Made Trisna Semara (Jurnal Ilmiah Hospitality Management, 2016)
This research aims to know the relationship of five pillars of tourism development in Nusa Penida, Klungkung regency, Bali. The method used in this research is qualitative method. The method is used to get data or descriptive explanation about the potency of tourism development and the role of five pillars in Nusa Penida. Data will be analized use descriptive qualitative analysis. The result of the research is the relationship of five pillars of tourism development (tourist attraction, accessibility, amenities, ancillaries, dan community involvement)in tourism development in Nusa Penida, Kabupaten Klungkung-Bali, have a positive effect to social, economic, and environment in Nusa Penida.